Analysis of the content of the preparatory and competitive microcycles of Algerian football clubs. : The case of the Mobilis Professional League 1 seniors, 2016/2017 Season - BENSALEM, Salem; MENELLA, Rachid; HOBARA, Mohamed (Journal of Human Sciences, 2022)
The main objective of this study is to provide an analysis of the content of the preparatory and competitive microcycles of Algerian football clubs. The investigation The survey of coaches in the first division (professional Mobilis league 1) 2016/2017 Season, focusing on the means and methods used in the preparation of footballers as well as the average volume of charges in the preparatory and competitive microcycles gave results 76 and 79 microcycle exercises in terms of resources; while the game method is the most preferred, while the interval training only comes in fourth position. Finally the weekly hourly volume varies from 240h07 ’to 380h20’depending on the period.